An Anomalous Antiaromaticity That Arises from the Cycloheptatrienyl Anion Equivalent. Issue 33 (27th June 2018) - Uehara, Keiji; Mei, Peifeng; Murayama, Tomohisa; Tani, Fumito; Hayashi, Hironobu; Suzuki, Mitsuharu; Aratani, Naoki; Yamada, Hiroko
Abstract : A fused azulene dimer with helicene‐like structure prepared by simple Suzuki–Miyaura coupling between naphthalene and azulene derivatives shows absorption in the near‐IR region up to 900 nm owing to the effective π‐expansion. The newly formed seven‐membered ring exhibits a positive NICS(1) value that arises from the antiaromatic cycloheptatrienyl anionic structure. Abstract : A fused azulene dimer with helicene‐like structure was prepared by simple Suzuki–Miyaura coupling between naphthalene and azulene derivatives. The newly formed seven‐membered ring exhibits a positive NICS(1) value that arises from the antiaromatic cycloheptatrienyl anionic structure.